Study on Smart Grid System Based on System Dynamics - Cui He-Rui; Xu Peng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Smart Grid is a large complex system, involving generation, transmission, distribution and delivery of four links. This paper analyzes the structure of the smart grid system in depth with a combination of qualitative and quantitative research approach. Then it explains state variables, rate variables and constants in the development of smart grid system under the Vensim software environment and analyzes subsystems causal feedback relationship in a macro point of view. Finally, this paper analyzes the simulation on the amount of funding and professionals in the smart grid system dynamics flow diagram after inputting DYNAMO language equations. The simulation analysis shows that the development of the smart grid should focus on training professionals. Professional talent is a source of strength in the smart grid development. At the same time, we should also pay attention to industrial policy related to the smart grid and seek break under the guidance of policy. http://dx.doi.org/10.11591/telkomnika.v12i12.5986